2015
DOI: 10.1007/s10826-015-0216-5
|View full text |Cite
|
Sign up to set email alerts
|

Can We Use Convergence Between Caregiver Reports of Adolescent Mental Health to Index Severity of Adolescent Mental Health Concerns?

Abstract: Clinical assessments of adolescent mental health often incorporate the perspectives of multiple caregivers (e.g., mothers and fathers). Caregiver reports tend to exhibit relatively high levels of correspondence versus other informant pairs such as caregivers and teachers. Yet, caregiver reports are not redundant with one another. Thus, researchers often apply strategies for integrating caregiver reports (e.g., composite score), assuming that greater convergence between caregivers on reports of high adolescent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
34
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 57 publications
3
34
0
Order By: Relevance
“…Moreover, there is a need to demonstrate measurement invariance when informant discrepancies are used as predictors. For example, a growing body of research uses differences in informant reports to predict mental health issues such as disruptive behavior ) and social anxiety (De Los Reyes et al 2013a), as well as global severity of mental health concerns (De Los Reyes et al 2016). By definition, invariant measures provide a more accurate picture of true differences across informants, and as a result, these differences should be more reliable predictors of a hypothetical outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, there is a need to demonstrate measurement invariance when informant discrepancies are used as predictors. For example, a growing body of research uses differences in informant reports to predict mental health issues such as disruptive behavior ) and social anxiety (De Los Reyes et al 2013a), as well as global severity of mental health concerns (De Los Reyes et al 2016). By definition, invariant measures provide a more accurate picture of true differences across informants, and as a result, these differences should be more reliable predictors of a hypothetical outcome.…”
Section: Discussionmentioning
confidence: 99%
“…As mentioned previously, prior work points to substantial dyad-level variations in magnitudes of convergence, including informant dyads who converge quite highly in reports of psychological phenomena (e.g., De Los Reyes et al 2009, 2013a, 2016aLippold et al 2011Lippold et al , 2013Lippold et al , 2014. What might convergence between these reports reflect?…”
Section: Converging Operations: When Adolescents' and Parents' Reportmentioning
confidence: 91%
“…For example, in adolescent mental health assessments, we have found that when two parents (i.e., informants who observe adolescents in the same context) converge on reports of relatively high adolescent mental health concerns, the adolescent both displays greater hostility within observed family interactions, and self-reports greater mental health concerns, relative to adolescents whose parents do not converge in their reports about adolescent mental health (De Los Reyes et al 2016a). Consistent with this work in mental health, in recent developmental work, adolescentparent dyads that converge on relatively low levels of parental knowledge have adolescents who are at particularly high risk for developing substance use (e.g., Lippold et al 2013Lippold et al , 2014.…”
Section: Converging Operations: When Adolescents' and Parents' Reportmentioning
confidence: 97%
See 2 more Smart Citations